Why Disrespectful Acts against Prophet Muhammad and Quran Must be Outlawed Worldwide: An Analysis of Legislations and Case Laws (Part 2) - Hopkinson, Eckhart Christopher (International journal of multicultural and multireligious understanding, 2025)
In this article, the discussion centers on the laws based on which the cartoons of the Prophet Muhammad, mocking, and insulting him, as well as any disrespectful acts against him or the Quran, should be banned globally. The discussion is based on previous rulings of the courts around the world trying similar cases. It has been shown that regarding similar cases, based on the courts’ own judgments, defamation, mocking, and insulting Prophet Muhammad is definitely hate speech. During the analysis of the case law, it can be seen that some criminal codes have been applied in an uneven way, particularly in the cases related to Prophet Muhammad, where the inconsistency in enforcement has been evident. Since the publication of the Danish Mohammed cartoons, a clear instance of double morality has emerged in how society applies the right to freedom of expression. For example, while cartoons depicting sensitive topics to Muslims, such as the prophet Mohammed, are commonly seen as justified exercises of this right, there is a striking contradiction in how cartoons on subjects sacred to Western secular society, notably the Holocaust, are often met with denunciation. Relevant domestic and international laws have been referenced in the accompanying supplementary file. Also, the relevant case law has been briefly summarized in the supplementary file. Each discussion of case law has been categorized according to the three-condition test established by the European Court of Human Rights (ECHR). This classification has facilitated the examination of each of these conditions in cases involving disrespectful acts towards Prophet Muhammad, the Quran, as well as Jesus and Saint Mary.